WHATSAPP SEBAGAI MEDIA KOMUNIKASI EFEKTIF DALAM PENDIDIKAN JARAK JAUH: TINJAUAN LITERATUR - Ayu Wulandari; Eka Haryati Yuliany (Jurnal Komunikasi, 2025)
The use of the instant messaging application WhatsApp as a communication medium in distance education has been a topic that has attracted the attention of many researchers in recent years. In today's digital era, this application not only serves as a means of communication between individuals but has also been integrated into the education system as a tool that enables eflective interaction between teachers and students. This article is a literature review that aims to examine the extent of WhatsApp's eflectiveness as a communication medium in distance education. By analysing various studies and literature sources, the article highlights benefits such as ease of access, the ability to deliver information in real-time, and opportunities for collaborative learning. On the other hand, it also identifies challenges that may be faced, including privacy and security concerns, the risk of information overload, and the need for discipline and good time management by users. The results of this literature review indicate that despite some challenges, the use of WhatsApp in the context of distance education oflers significant potential to improve communication and learning interactions, provided proper implementation and consideration of related issues are managed well